Diabetes and the Heart - Vinall, Phil (MD Conference Express, 2009)
This article discusses the therapeutic challenges that are associated with the combination of coronary artery disease (CAD) and diabetes mellitus. The link between CAD and dysglycemia is that the release of stress hormones and peptides due to a myocardial infarction is associated with insulin resistance and increased glucose or free fatty acid levels.